OPTICAL COHERENCE TOMOGRAPHY ANGIOGRAPHY FINDINGS IN TWO CASES OF SOLAR RETINOPATHY. Issue Volume 15:Issues 6(2021) (November 2021) - Padidam, Sneha; Burke, Marie T.; Apple, Daniel B.; Suchomel, John R.; Lin, Xihui
Abstract : Purpose: To report optical coherence tomography angiography findings obtained in two patients with solar retinopathy. Methods: Two case reports. Results: Two patients presented with blurry vision after sun gazing during the recent solar eclipse and were found to have characteristic foveal lesions on examination and optical coherence tomography consistent with solar retinopathy. Optical coherence tomography angiography showed a focal area of nonperfusion of the choriocapillaris in the affected eyes. Conclusion: Changes to the choriocapillaris layer on optical coherence tomography angiography in two patients with solar retinopathy suggest that damage is not limited to the retina. Abstract : Optical coherence tomography angiography in patients with solar retinopathy shows focal vessel dropout in the choriocapillaris suggesting that damage in solar retinopathy is not restricted to the outer retina and retinal pigment epithelium.